2017
DOI: 10.1111/1462-2920.13637
|View full text |Cite
|
Sign up to set email alerts
|

The chimeric nature of the genomes of marine magnetotactic coccoid‐ovoid bacteria defines a novel group ofProteobacteria

Abstract: Magnetotactic bacteria (MTB) are a group of phylogenetically and physiologically diverse Gram-negative bacteria that synthesize intracellular magnetic crystals named magnetosomes. MTB are affiliated with three classes of Proteobacteria phylum, Nitrospirae phylum, Omnitrophica phylum and probably with the candidate phylum Latescibacteria. The evolutionary origin and physiological diversity of MTB compared with other bacterial taxonomic groups remain to be illustrated. Here, we analysed the genome of the marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 61 publications
1
45
0
Order By: Relevance
“…So far, cultured and uncultured MTB A from freshwater and marine environments belong to the following three genera within a single family: the Magnetospirillum, Magnetovibrio and Magnetospira genera within the Rhodospirillales (Lefèvre et al, 2013a). Indeed, recent comparative genomic analyses concluded that Magnetococcalesonce classified in Alphaproteobacteriashall be considered as a new class of Proteobacteria (i.e., "Candidatus Etaproteobacteria") (Ji et al, 2017;Lin et al, 2018). In the Alphaproteobacteria class, phylogenies based on neutral markers rather support the scenario of a clonal inheritance of magnetosome genes within and between genera (Lefèvre et al, 2013a), despite the genetic evidences compatible with HGTs found in some MTB A genomes (Jogler et al, 2009;Rioux et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…So far, cultured and uncultured MTB A from freshwater and marine environments belong to the following three genera within a single family: the Magnetospirillum, Magnetovibrio and Magnetospira genera within the Rhodospirillales (Lefèvre et al, 2013a). Indeed, recent comparative genomic analyses concluded that Magnetococcalesonce classified in Alphaproteobacteriashall be considered as a new class of Proteobacteria (i.e., "Candidatus Etaproteobacteria") (Ji et al, 2017;Lin et al, 2018). In the Alphaproteobacteria class, phylogenies based on neutral markers rather support the scenario of a clonal inheritance of magnetosome genes within and between genera (Lefèvre et al, 2013a), despite the genetic evidences compatible with HGTs found in some MTB A genomes (Jogler et al, 2009;Rioux et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar analyses have been performed in the genomes of Alphaproteobacteria (Esser et al, 2007), and great variation in the data (between 33 and 97%) pointed out a chimeric trait of several alphaproteobacterial genomes. In addition, this strategy, combines to other evolutionary analyses, has been recently used to define a novel group of Proteobacteria, named Etaproteobacteria (Ji et al, 2017). These current data demonstrated, for the first time, that the top-scoring Blast analysis can be useful to define or confirm that a set of organisms belong to a particular taxonomic groups.…”
Section: Resultsmentioning
confidence: 99%
“…More than 10 OTUs corresponded to this bacterium. The function of this bacterium is not well defined; it was previously identified in an anammox community [60] and might be related to Magnetotactic bacteria [61]. Samples PM7 and OTA4 were associated with high NO 3 − and low Mn 2+ , which suggests that these samples were in the denitrification phases.…”
Section: The Influence Of Electron Acceptors On Bacterial Communitiesmentioning
confidence: 93%